Motivasi Pustakawan dalam Mengikuti Kegiatan Diklat Training Or Trainers (TOT) - Sutriono Sutriono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine both intrinsic and extrinsic motivations that encourage librarians to take part in the 2019 Training For Trainers (TOT) training activities which are held for 20 days and are followed by librarians who have entered the age above fifty years. The method used in this research is descriptive qualitative. The sample in this study were 30 librarians taken by total sampling. The data needed is obtained by interview and direct observation in the field. The results of the study, as many as 18 respondents (60%) conveyed the motivation to follow TOT derived from internal factors, from these internal factors as many as 18 respondents (60%) claimed to want to improve their insights and skills about librarian training, as for external factors because they wanted to get SIM / legality to teach librarian technical / functional training recognized by 16 respondents (53%). In conclusion, the strongest motivation behind the librarian following the 2019 Training For Trainers (TOT) training activity was the need to add insight and skills to become library trainers / instructors, in addition to getting legality in teaching technical / functional librarian training. Keywords: Learning Soul, Librarian Motivation, Training of Trainers